Floating Nuclear Power Plants in Russia: A Threat to the Arctic, World Oceans and Non- Proliferation Treaty - Kuznetsov V. M.; Yablokov A. V.; Kolton I. B.; Simonov E. J.; Desyatov V. M.; Forofontov I. V.; Nikitin A. K. (Москва, Agency Rackurs Production, 2004)
A brief description is given of the floating nuclear power plants (FNPPs) which are currently being developed in Russia and an analysis is made of the environmental, economic and political consequences of the implementation of this FNPP project by the Russian Ministry of Atomic Energy (Minaton). The main conclusions which are drawn are as follows: floating nuclear power plants pose a potential danger to the environment; their profitability is highly questionable; the realization of the FNPP project would create a situation in which nuclear fissile materials suitable for the production of nuclear weapons were much more easily available, thereby undermining the nuclear non-proliferation treaty; and the potential for international nuclear espionage and terrorism would be grea ly increased. Furthermore, violations of operating regulations at haval nuclear installations are highlighted and an analysis is made of Russian Normative Documents govering nuclear and radiation safety for naval nuclear installations. This publication is written for a wide readership interested in the issues of nuclear and radiation safety, the global ecology, the Arctic and the World Oceans. This edition has been issued with the support of Green Cross Switzerland and the Nuclear and Radiation Safety Programs of Green Cross Russia.